Класифікація патологічних ЕЕГ-сигналів за допомогою методів машинного навчання - Білошицька, Оксана Костянтинівна (НТУ "ХПІ", 2017)
Робота присвячена застосуванню методів машинного навчання при створенні моделі класифікації патологічних сигналів ЕЕГ. Сформовано ефективний набір ознак, які є пріоритетними під час класифікації сигналів з епілептиформною та нормальною активністю головного мозку. Встановлено, що застосування методу опорних векторів дає точність класифікації 80 %, методу лінійного дискримінантного аналізу – 91 %, методу випадкового лісу – 96 % та методу Extra trees – 91 %. Побудована комплексна модель на основі даних методів дала результуючу точність 89 %.

Epilepsy is the fourth most common neurological problem in the world. When diagnosing epilepsy, the most informative is the registration of EEG, which helps distinguish epileptic seizures from non˗epileptic seizures and classify them. As a result of the preliminary processing of raw data of EEG signals, segments of signals with epileptic activity were isolated separately, and signals without pathological rhythms were divided into segments of 30 seconds duration. A database of 194 signals with epileptiform activity and 194 signals of normal brain activity was obtained. Performed preprocessing of EEG, an effective set of characteristics has been generated for the classification of signals with epileptiform and normal activity of brain; a model for the classification of pathological EEG signals was created and based on methods of machine learning. An effective set of characteristics has been generated for the classification of signals with epileptiform and normal activity of brain. A model for classifying pathological EEG signals was created in the software environment Python 2.7.5. Model consisted of methods Support Vector Machine, Linear Discriminant Analysis, Random Forest and Extra trees. The constructed complex model on these methods has shown the resulting accuracy of 89 %.
Classification of pathological EEG signals using machine learning methods
Keywords: метод опорних векторів; аналіз лінійний; аналіз дискримінантний; ліс випадковий; Extra trees; support vector machine; linear discriminant analysis; random forest